Association between neighborhood food environment and dietary diversity score among older people in Beijing, China: A cross-sectional study - Zhang, Man; Zhang, Na; Zhou, Mingzhu; Ma, Guansheng (Frontiers in Nutrition, 2022)
Objective To examine the association between the neighborhood food environment and dietary diversity score (DDS) among elderly people in China. Methods Participants were recruited from 12 communities in Beijing, China, in 2019, using a multi-stage stratified random sampling method. Participants (n = 1,764, 730 men) in this study were elderly people aged 65 to 80. A questionnaire survey was used to investigate the intake of various foods in the past 3 days, and their dietary diversity score (DDS) was calculated. Baidu Map Application Programming Interface was used to measure the neighborhood food environments, including the density of and proximity to different food outlets. Adjusted multiple linear regression was performed to estimate the association between the neighborhood food environment and DDS. Results A total of 1,800 questionnaires were distributed, and 1,775 questionnaires were returned. The questionnaire response rate was 98.6%. Among them, the number of valid questionnaires was 1,764, and the valid rate was 99.4%. The mean age of the participants was 69.7 ± 4.3, and the average DDS was 7.2 ± 1.4. Among the three types of stores, convenience stores had the best access, followed by greengrocers, and finally supermarkets. Sit-down restaurants had the nearest walking distance, Chinese fast-food restaurants had the largest number, and western fast-food restaurants were the most difficult to access. Better access to supermarkets tended to be associated with higher DDS score within all the buffer zones (250 m buffer zone: β = 0.495, P < 0.001; 500 m buffer zone: β = 0.341, P < 0.001; 800 m buffer zone: β = 0.163, P < 0.001; 1,000 m buffer zone: β = 0.243, P < 0.001). However, greengrocers were negatively associated with DDS score within all the buffer zones (250 m buffer zone: β = −0.475, P < 0.001; 500 m buffer zone: β = −0.161, P < 0.001; 800 m buffer zone: β = −0.090, P < 0.001; 1000 m buffer zone: β = −0.112, P < 0.001). As for convenience stores, we only found significant results within the 250 m buffer zone (β = 0.075, P = 0.002). Among the three types of restaurants, the results were inconsistent within different buffer zones. Sit-down restaurants were negatively associated with DDS score within 250 m buffer zone (β = −0.257, P < 0.001), and positively associated with DDS score within 1,000 m buffer zone (β = 0.018, P < 0.001). Living in areas with more Chinese fast-food restaurants tended to have higher DDS within 250 m buffer zone (β = 0.357, P < 0.001); however, there was a opposite result within 1,000 m buffer zone (β = −0.044, P < 0.001). Better access to western fast-food restaurants tended to be associated with lower DDS score within 500 m buffer zone (β = −0.235, P < 0.001) and higher DDS score within 1,000 m buffer zone (β = 0.189, P < 0.001). There was a negative correlation between the nearest distance to the supermarket and the DDS score (β = −0.002, P < 0.001), and the nearest distance to the greengrocer was directly positively correlated with the DDS score (β = 0.004, P < 0.001). Conclusion This study suggests that supermarkets may increase the DDS score among older adults in Beijing, while greengrocers may reduce the DDS score. However, the current results are not strong enough to draw specific conclusions. Policymakers need to rely on more evidence to make specific policy recommendations.